2018
DOI: 10.1016/j.ccell.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anti-lymphoma Activity of CAR19-iNKT Cells Underpinned by Dual CD19 and CD1d Targeting

Abstract: SummaryChimeric antigen receptor anti-CD19 (CAR19)-T cell immunotherapy-induced clinical remissions in CD19+ B cell lymphomas are often short lived. We tested whether CAR19-engineering of the CD1d-restricted invariant natural killer T (iNKT) cells would result in enhanced anti-lymphoma activity. CAR19-iNKT cells co-operatively activated by CD1d- and CAR19-CD19-dependent interactions are more effective than CAR19-T cells against CD1d-expressing lymphomas in vitro and in vivo. The swifter in vivo anti-lymphoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(136 citation statements)
references
References 59 publications
1
129
0
1
Order By: Relevance
“…In this scenario, the infusion of allogeneic CAR T cells could carry the theoretical risk of GvHD; however, incidence of this fearsome complication in early trials was quite low, and an elegant study in mouse models showed that the CAR-driven and TCR-driven signal actually adds up, accelerating exhaustion and limiting alloreactions (101). Still, a number of studies are focusing on the development of improved strategies to further enhance CAR T efficacy and persistence without risking to induce GvHD, such as by transducing recipient-derived donor T cells (113), by using genome editing approaches to knock out the endogenous TCR (101, 114), or by modifying with the CAR different immune cells, less prone to induce GvHD (85,115,116).…”
Section: Adoptive Immunotherapy With Genetically Redirected Immune Cellsmentioning
confidence: 99%
“…In this scenario, the infusion of allogeneic CAR T cells could carry the theoretical risk of GvHD; however, incidence of this fearsome complication in early trials was quite low, and an elegant study in mouse models showed that the CAR-driven and TCR-driven signal actually adds up, accelerating exhaustion and limiting alloreactions (101). Still, a number of studies are focusing on the development of improved strategies to further enhance CAR T efficacy and persistence without risking to induce GvHD, such as by transducing recipient-derived donor T cells (113), by using genome editing approaches to knock out the endogenous TCR (101, 114), or by modifying with the CAR different immune cells, less prone to induce GvHD (85,115,116).…”
Section: Adoptive Immunotherapy With Genetically Redirected Immune Cellsmentioning
confidence: 99%
“…Administration of alpha-galactosylceramide (αGC), a ligand for iNKT cells, or αGC-pulsed DCs inhibits tumor growth in both mouse models and human patients [5][6][7][8] . Moreover, recent studies report a notable anti-tumor efficacy of CAR iNKT cells 9,10 . However, not all patients respond to these iNKT cell-based immunotherapies 7,8 .…”
mentioning
confidence: 99%
“…The application of 8D4-8 in studies where users did not know it bound a unique apoptosis-associated target presents a sizable issue. In evaluating the literature for IL-4 expression measured by flow cytometry in the time since the publication of 8D4-8, we found multiple publications reported using this clone (Prussin and Metcalfe, 1995; Fukui et al, 1997; Kallas et al, 1998; Kon et al, 1998; Schulze-Koops et al, 1998; Furlan et al, 2000; Kipp et al, 2000; Johansson-Lindbom and Borrebaeck, 2002; Rutella et al, 2002; Ryan et al, 2002; Sugimoto et al, 2002; Walker et al, 2002; Hashizume et al, 2005; Kilani et al, 2005; Nakamura et al, 2005; Acosta-Rodriguez et al, 2007; Ito et al, 2008; Delgado et al, 2009; Godefroy et al, 2011; Saito et al, 2011; Truchetet et al, 2011; Caccamo et al, 2012; Miguel et al, 2012; Baeck et al, 2013; LaVoy et al, 2013; Myklebust et al, 2013; Qiu et al, 2013; Jergovi et al, 2014; Mattoo et al, 2014; Periolo et al, 2014; MacDonald et al, 2015; Wang S. et al, 2015; Wang Z. et al, 2015; Coraglia et al, 2016; De Biasi et al, 2016; Li et al, 2016; Vacaflores et al, 2016; Wang et al, 2016; Hou et al, 2017; Powell et al, 2017; Rouxel et al, 2017; Fox et al, 2018; Kim et al, 2018; Kwok et al, 2018; Maselli et al, 2018; Rotolo et al, 2018; Sureshchandra et al, 2018; Mann et al, 2019; Schreurs et al, 2019). This list should not be considered exhaustive as some publications may have been missed and many reports evaluating IL-4 did not mention which clone was used.…”
Section: Discussionmentioning
confidence: 99%